Gear Wear Mechanisms, Monitoring Techniques and Their Potential Use in Gear Predictive Maintenance - Marek Stembalski; Tomasz Jankowski; Andrzej Roszkowski; Waclaw Skoczynski (Journal of Machine Engineering)
In order to ensure the undisturbed operation of gear transmissions, avoid their unplanned downtimes and secondary damage to them, their condition needs to be monitored and their failures need to be diagnosed. Currently, there is no commercial and universal diagnostic system for predictive analysis of gear wear. There are also no limit values of wear indicators defining individual causes of wear. The article presents problems related to various mechanisms of gear wear. Different methods of monitoring the condition of the gear are presented. They are presented. Thermal methods, analysis of wear residues, and measurements and analysis of vibrations and acoustic emissions are described. The usefulness of these techniques for predictive maintenance of gear movement is indicated. It is proposed to extend gear diagnostics by using machine learning methods to detect their faults, and in particular critical states of gear wear.